2011
DOI: 10.1007/s12032-011-9984-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9) and aminopeptidase N/CD13 in breast cancer patients

Abstract: The aim of this study was to analyse the expression of matrix metalloproteinase-2(MMP-2), matrix metalloproteinase-9 (MMP-9) and aminopeptidase APN/CD13 in breast carcinoma samples, and their possible prognostic value in breast cancer patients. The expression of MMP-2, MMP-9 and APN/CD13 in tumor cells was analysed in 138 breast carcinomas by immunohistochemical staining of tumor cells using the semiquantitative method for the detection of cytoplasmic and membrane reaction in tumor cells as well as stromal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 34 publications
0
50
1
Order By: Relevance
“…The remaining 29 papers were approved through scrutinizing the entire paper. Among the 29 papers, five literatures had no sufficient data to analyze (Remacle et al, 1998;Wang et al, 2002;Casar et al, 2010;Mohammad et al, 2012;Ranogajec et al, 2012). MMP-9 protein expression was measured in serum in five studies (Lepp et al, 2004;Lepp et al, 2005;Mattilaet al, 2005;Quaranta et al, 2007;Sung et al, 2012) and one study measured MMP-9 expression in plasma (Ranuncolo et al, 2003).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 29 papers were approved through scrutinizing the entire paper. Among the 29 papers, five literatures had no sufficient data to analyze (Remacle et al, 1998;Wang et al, 2002;Casar et al, 2010;Mohammad et al, 2012;Ranogajec et al, 2012). MMP-9 protein expression was measured in serum in five studies (Lepp et al, 2004;Lepp et al, 2005;Mattilaet al, 2005;Quaranta et al, 2007;Sung et al, 2012) and one study measured MMP-9 expression in plasma (Ranuncolo et al, 2003).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Both tumor cell and stromal tissues in breast cancer tissue have been reported to have increased MMP-9 expression (Ranogajec et al, 2012). A considerable number of studies have proved that high MMP-9 expression is related to tumor stage and lymph node metastasis in breast cancer patients (Hanemaaijer et al, 2000;Hao et al, 2007;Gu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, both DFS and OS were worse in the presence of MMP-2 and absence of ER (p=0.012 and p=0.005, respectively) ( Figure 2 C and D). Ranogajec et al (2012) studied MMP-2 in breast cancer, and OS was significantly shorter in patients with positive MMP-2. 24 Recently, Min et al 17 correlated the MMP-2 expression pattern with ER and PR, but did not show a correlation with DFS or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Ranogajec et al (2012) studied MMP-2 in breast cancer, and OS was significantly shorter in patients with positive MMP-2. 24 Recently, Min et al 17 correlated the MMP-2 expression pattern with ER and PR, but did not show a correlation with DFS or OS. In another study that used single nucleotide polymorphism analysis (SNP), the authors suggest that MMP-2 can influence patient survival as an independent factor, attenuating the metastatic potential and augmenting survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, several studies have found that MMP-2 expression in tumor cells was associated with shortened disease-free survival (DFS), recurrence-free survival (RFS), or overall survival (OS; refs. [19][20][21][22][23], whereas few others have suggested inconsistent results (24,25). Although there were several studies on the association between the levels of serum MMP-2 and clinicopathologic factors, the results were inconsistent across the studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%